2017
DOI: 10.1002/lary.26513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a revised indication for determining adult cochlear implant candidacy

Abstract: Objective: To evaluate the use of monosyllabic word recognition versus sentence recognition to determine candidacy and long-term benefit for cochlear implantation. Study Design: Prospective multi-center single-subject design. Methods: A total of 21 adults aged 18 years and older with bilateral moderate to profound sensorineural hearing loss and low monosyllabic word scores received unilateral cochlear implantation. The consonant-nucleus-consonant (CNC) word test was the central measure of pre- and postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 35 publications
3
55
2
Order By: Relevance
“…The results are similar to those for other languages [3,4,9]. In addition, CI users' scores on the iCI2004 were slightly worse than those on the 67-S [13,15].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results are similar to those for other languages [3,4,9]. In addition, CI users' scores on the iCI2004 were slightly worse than those on the 67-S [13,15].…”
Section: Discussionsupporting
confidence: 84%
“…the Vibrant SoundBridge, BONEBRIDGE, and bone-anchored hearing aids), and electric acoustic stimulation (EAS) have dramatically improved the hearing thresholds even in people with profound hearing loss. To measure the effects of hearing aid (HA) and hearing implant use, speech perception tests are commonly used as indices reflecting hearing ability in daily life in many countries [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The results described above endorse the idea that in countries that hold on to more conservative criteria for CI candidacy, expansion of CI indication is beneficial for long-term benefit [ 2 4 , 28 , 29 ]. CI performance has improved and more evidence was found for the positive effect of residual hearing on CI outcome, strengthening the growing need for a shift of CI indication.…”
Section: Discussionsupporting
confidence: 67%
“…Referencing the clinical MSTB measures, the upper cutoff for those expressing need for a second implant was 30% CNC, 45% AzBio quiet, and 18% AzBio in noise at +5 dB SNR. There is a precedent for choosing 30% CNC word recognition for determining ear specific CI candidacy as two North American multi-site studies-Nucleus Freedom (Balkany et al 2007) and Cochlear Revised Indications Study (Sladen et al 2017)-both used 30% CNC word recognition in the ear to be implanted as the criterion guiding CI candidacy. Furthermore, both studies demonstrated significant speech recognition benefit for the CI recipients using this criterion.…”
Section: Discussionmentioning
confidence: 99%